2014
DOI: 10.4037/ccn2014416
|View full text |Cite
|
Sign up to set email alerts
|

Closed Blood Conservation Device for Reducing Catheter-Related Infections in Children After Cardiac Surgery

Abstract: BACKGROUND Arterial catheters are potential sources of nosocomial infection. OBJECTIVE To investigate use of a closed blood conservation device in preventing catheter-related bloodstream infections in children after cardiac surgery. METHODS Children with an indwelling arterial catheter after cardiac surgery were randomly assigned to 2 groups: a control group with a conventional 3-way stopcock in the catheter system and an interventional group with the conservation device in the catheter system. Catheter tips, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 34 publications
0
7
0
Order By: Relevance
“…closed systems, needleless connectors). [32][33][34] There are theoretical concerns regarding the reinfusing of line clearance fluid and the risk for hub contamination and thrombosis. There are some conditions for which the reinfusion of this fluid causes unacceptable risk of complication (e.g.…”
Section: Clinical Practice Guidelinesmentioning
confidence: 99%
“…closed systems, needleless connectors). [32][33][34] There are theoretical concerns regarding the reinfusing of line clearance fluid and the risk for hub contamination and thrombosis. There are some conditions for which the reinfusion of this fluid causes unacceptable risk of complication (e.g.…”
Section: Clinical Practice Guidelinesmentioning
confidence: 99%
“…Previous studies have shown that closed infusion systems are associated with a decrease in overall CLABSI rates when compared to open infusion systems. Other studies have proposed that closed blood sampling systems, such as the venous arterial blood management and protection (VAMP™) and KidsKit™ systems, decrease system entry, blood waste, and microbial contamination (56)(57)(58). A pediatric study evaluated both systems and compared implementation of the KidsKit™ system to the conventional three-way stopcock methods used on umbilical arterial catheters in the PICU and NICU.…”
Section: Question 2: How Often Should Cvc Dressings Be Changed In Nic...mentioning
confidence: 99%
“…Other studies have proposed that closed blood-sampling systems, such as the venous arterial blood management and protection (VAMP TM ) and KidsKit TM systems, decrease system entry, blood waste, and microbial contamination. [55][56][57] A pediatric study evaluated both systems and compared implementation of the KidsKit system to the conventional 3-way stopcock methods used on umbilical arterial catheters in the PICU and NICU. The authors found a decrease in CLABSIs below the national benchmark.…”
Section: • If Other Interventions Have Failed To Reduce Clabsi In An ...mentioning
confidence: 99%
“…The use of a closed blood conservation device, the venous arterial blood management protection system, decreases the incidence of catheter-related contamination of the intraluminal fluid. [ 26 ]…”
Section: Strategiesmentioning
confidence: 99%